The Agricultural Extension Officer’s Qualification and Role in Farmers’ Groups Receiving Government Assistances in Padang City, West Sumatra - Amrizal Anas; Aditya Alianta; Ediset Ediset (Andalasian International Journal of Agriculture and Natural Sciences (AIJANS), 2025)
The study was conducted to identify the qualifications and describe the roles of Agricultural Extension Officers in livestock farmer groups receiving government assistance in Padang City, West Sumatra. The study employed a rigorous survey approach, supported by a questionnaire and field observations, to gather data. The focus was on farmer groups benefiting from government support. A purposive sample was determined to consist of 6 livestock groups: 2 cattle farmer groups, 2 goat farmer groups, and 2 poultry farmer groups. Data were analysed and presented in a statistical descriptive quantitative format. The results indicated that the communication skills of extension agents were categorised as moderate, while their attitudes, knowledge, and adaptability were rated as good. Extension officers were found to play effective roles in education, facilitation, supervision, and evaluation, although their roles in dissemination, consultation, and advocacy were moderate. In conclusion, Agricultural Extension Officers were determined to have suitable qualifications and roles in conducting extension services within government-assisted livestock farmer groups in Padang City, West Sumatra.